Low gain avalanche diodes for photon science applications - Centis Vignali, Matteo; Paternoster, Giovanni (Frontiers in Physics, 2024)
Low Gain Avalanche Diodes (LGADs) are silicon sensors designed to achieve an internal gain in the order of 10 through the impact ionization process. The development of LGADs was pushed forward by their application in High Energy Physics (HEP) experiments, where they will be employed to provide measurements of the time of arrival of minimum ionizing particles with a resolution of around 30 ps. The initial technological implementation of the sensors constrains their minimum channel size to be larger than 1 mm 2 , in order to reduce inefficiencies due to the segmentation of the gain structure. The gain of the sensors is kept in the order of 10 to limit the sensor shot noise and their power consumption. In photon science, the gain provided by the sensor can boost the signal-to-noise ratio of the detector system, effectively reducing the x-ray energy threshold of photon counting detectors and the minimum x-ray energy where single photon resolution is achieved in charge integrating detectors. This can improve the hybrid pixel and strip detectors for soft and tender x-rays by simply changing the sensor element of the detector system. Photon science applications in the soft and tender energy range require improvements over theLGADs developed for HEP, in particular the presence of a thin entrance window to provide a satisfactory quantum efficiency and channel size with a pitch of less than 100 µm. In this review, the fundamental aspects of the LGAD technology are presented, discussing also the ongoing and future developments that are of interest for photon science applications.